Upaya Pemberdayaan Peternak Kambing Etawa Melalui Komunitas Kampong Kopi Lerek Gombengsari (Lego) - Maharani, Dian; Hariyono, Syech (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2021)
The empowerment efforts on Etawa goat farmers through Lerek Gombengsari Coffee Community in Lerek hamlet, Gombengsari village, Kalipuro sub-district, Banyuwangi regency is in the form of empowerment in the field of livestock. Therefore, this research was aimed to describe the empowerment efforts on Etawa goat farmers through Lerek Gombengsari Coffee Community in Lerek Hamlet, Gombengsari village, Kalipuro sub-district, Banyuwangi Regency, East Java Province. This descriptive research employed a qualitative approach. The research informants were determined purposively. Research data were collected through observation, semi-structured interviews, and documentation. Then, the data were analyzed by using data collection, data reduction, data display, and verification/ conclusion. To test data validity, the researchers used source, method, and time triangulations. The findings indicated that the empowerment efforts were the awareness of the Etawa goat farmers and increasing the knowledge, the skills, the attitude, the capacity, the income, and the welfare of Etawa goat farmers.